PENGELOLAAN LIMBAH CAIR PETERNAKAN SAPI DENGAN INTERVENSI OXIDATION POND UNTUK MENYELESAIKAN PERMASALAHAN BAU DAN RISIKO KONTAMINASI BADAN AIR - Mubayyina Mukhlis; Munawar Ali (EnviroUS, 2021)
Water from cattle farming operations that is not properly managed and discharged directly into the environment can cause unpleasant odors and increase the risk of contamination of surrounding water bodies. The purpose of this study was to determine an effective management system in solving odor problems and the risk of contamination of water bodies. The method in this research includes the design of a management system and laboratory-scale processing experiments involving the oxidation pond as the processing unit. The cattle farm liquid waste management system consists of 3 stages, namely pre-treatment, primary treatment, and secondary treatment, where there is a processing unit (oxidation pond) for secondary treatment. Wastewater is treated in the oxidation pond with a variation of the injected oxygen discharge of 6 L / minute, 8 L / minute, and 11 L / minute with residence time during the calculation time according to EPA / 600 / R-11/008 of 2011 (respectively 0.256 days, 0.1356 days, 0.1096 days), 3 days, 7 days, and 14 days were equipped with control of oxidation-reduction potential (ORP) values. The parameters observed were odor, Biochemical Oxygen Demand (BOD) and Total Ammonia (NH3-N). Where the wastewater after the treatment process is yellowish with low turbidity and has no smell. While the test results after the study showed that the average BOD level had met the quality standard. With the highest final BOD level was 152 mg / L and the lowest was 98 mg / L. Meanwhile, the highest total ammonia levels after research were 0.0088 mg / L and the lowest was 0.00032 mg / L. Management with an oxidation pond as a processing unit is effective in overcoming odor problems and reducing levels of BOD and ammonia pollutants.